La fractocomposition en français et en tchèque : le cas de ‑gate - Mudrochová, Radka; Koláříková , Dagmar (Studia Romanica Posnaniensia, 2023)
The objective of this contribution is to contrastively analyze the currency of words formed by the frac- tolexeme -gate in French and Czech languages. Before presenting the results of our research that relies especially on data derived from the SketchEngine (Czech Web 2017; French Web 2017) corpora, we find it necessary to address theoretical questions to frame the concept of fractocomposition in current linguistic studies. We have borrowed the term fractocomposition from the French linguist Jean-François Sablay- rolles (2019, p. 149), who defines it as a case of compounds “one of whose elements is a fractolexeme, a fragment of lexie which is valid for the entire lexie”. However, in our discussion we note also other terms that are also used to denote the same concept.